(untitled) (Práxis Educativa, 2023)
This article aims to analyse the role of school leaders in mediating education accountability policies in Brazil. The study is framed by a sense-making and contingent leadership framework and is guided by a ‘realist evaluation’ methodological approach. The qualitative research conducted in four schools in Belo Horizonte shows that school leaders play a substantial role in mediating how school accountability reforms are received. They enact different roles, behaviours and practices, shaped by the sense-making and perception of accountability reforms and dependent upon three main contingent factors: leaders’ positional power and gender, socio-economic school composition and schools’ administrative dependency. Keywords: School leadership. Brazil. Test-based accountability policy.